Clinical applications of MS-based protein quantification - Sabbagh, Bassel; Mindt, Sonani; Neumaier, Michael; Findeisen, Peter (Proteomics. Clinical applications, 2016)
Mass spectrometry-based assays are increasingly important in clinical laboratory medicine and nowadays are already commonly used in several areas of routine diagnostics. These include therapeutic drug monitoring, toxicology, endocrinology, pediatrics, and microbiology. Accordingly, some of the most common analyses are therapeutic drug monitoring of immunosuppressants, vitamin D, steroids, newborn screening, and bacterial identification. However, MS-based quantification of peptides and proteins for routine diagnostic use is rather rare up to now despite excellent analytical specificity and good sensitivity. Here, we want to give an overview over current fit-for-purpose assays for MS-based protein quantification. Advantages as well as challenges of this approach will be discussed with focus on feasibility for routine diagnostic use.
Gesehen am 23.04.2019